THE EFFECT OF ONLINE CONSUMER INTERACTION AND SHOPPING MOTIVATION ON PURCHASE INTENTION - Kunthi Kusumawardani; Poppy Purniasari (President University, 2021)
Consumer interaction has become more important than ever. The interaction may happen on various platforms, for instance, brand webpage and social media. This study aims to examine the consumer interaction and shopping motivation on purchase intention mediated by EWOM, brand awareness, and brand attitude in the beauty products context. After gathered 300 valid respondents, this study used Structural Equation Modelling (SEM) to analyze the data. The results showed that purchase intention is influenced directly by E-WOM, opinion seeking, annoyance, and brand attitude. Besides, E-WOM is mediating brand page commitment and annoyance to purchase intention. Interestingly, viral advertisement, brand awareness, and brand page commitment do not influence purchase intention directly. Research implications and directions for future studies are discussed.